Usability Evaluation of Mobile USSD-SMS Interactive Result Checking System for Resource-Constrained Settings (MIRCS) using System Usability Score (SUS). - Muhammad, Zainab Tassala; Kawu, Abdullahi Abubakar; Abdullahi, Ibrahim; Bawa, Musa (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Mobile phones, especially smartphones have impacted the way we access information related to education. For instance, students are now able to view their results using a smartphone on a browser. However, these result systems that make it possible for students to view their exam results through web browsers or emails on their mobile devices need an internet connection for the process to work as expected. Also, given the indigent nature of most students in developing countries, this creates a digital divide for students that do not own smartphones. With many students coming from rural and often low economic status homes, not many can afford smartphones. Hence, leveraging on the potentials of Unstructured Supplementary Service Data (USSD) and Short Message Service (SMS), a Mobile USSD-SMS Interactive Result Checking System for Resource-Constrained Settings (MIRCS) was developed to provide a device agnostic accessible Result Checking System. This study evaluated MIRCS using System Usability Scale (SUS) to verify the effectiveness from a usability point of view. The result of the evaluation shows that the MIRCS is usable which received grade C (66.21), although it does not meet the acceptable level specified by SUS. Further analysis of the interaction with respondents suggests some areas of improvement to include cost of service, high availability and accuracy.